2011
DOI: 10.1177/003335491112600316
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis of the Determinants of Pre-Hypertension and Hypertension in Rural Southwest China

Abstract: This article on determinants of pre-hypertension and hypertension in rural southwest China is an interesting study with more than 11,000 subjects. The finding that pre-hypertension is more prevalent than hypertension provides evidence of the need for early intervention in the population and intervention strategies that are appropriate for the diverse ethnic groups that exist within the population. As the authors note, the prevalence of hypertension has risen in the last decade in China. This increase follows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…From 2001 to 2010, the prevalence of pre-hypertension decreased, whereas the prevalence of hypertension increased with increasing age, which is consistent with other studies [ 13 , 15 33 , 34 ]. Males had a higher prevalence of pre-hypertension but a lower prevalence of hypertension, particularly in 2010, demonstrating a trend similar to that reported for the subgroup aged 65–74 by Gu et al [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…From 2001 to 2010, the prevalence of pre-hypertension decreased, whereas the prevalence of hypertension increased with increasing age, which is consistent with other studies [ 13 , 15 33 , 34 ]. Males had a higher prevalence of pre-hypertension but a lower prevalence of hypertension, particularly in 2010, demonstrating a trend similar to that reported for the subgroup aged 65–74 by Gu et al [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among the individual level non-modifiable factors, age, sex and marital status are found to be significantly associated with hypertension. Similar to the previous studies, older participants, males, widowed, divorced and separated, Christians and Muslims, scheduled tribes, low educated and wealthier respondents are more likely to be hypertensive[ 24 26 ].…”
Section: Discussionsupporting
confidence: 75%
“…socio-economic characteristics, health and lifestyle practices). On the contrary, at the community level a higher value of VPC (13% to 14%) shows a higher rate of variation in the prevalence of hypertension and can be attributed to the effects of background factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence of chronic diseases has risen rapidly in the last decade. This increase has been followed by a worldwide trend in the consideration of the growing burden of non-communicable diseases as a serious public health concern [ 5 ]. As recent studies have shown, the burden of chronic diseases can increase considerably as the population ages [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%